ESRA19-0288 Hip arthroscopy – is the pericapsular nerve group block approach plus a subpectineal injection the key to successful analgesia? Two case reports. (30th August 2019) - Silva, R; Almeida, P; Veiga, J; Castro, J; Lakhani, R; Ribeiro, L; Fragoso, P
Abstract : Background and aims: Hip arthroscopy is a minimally invasive surgical procedure which requires early ambulation for successful rehabilitation. Regional techniques selectively blocking the sensitive branches of the hip joint may provide reasonable analgesia with minor motor block. We report two cases of hip arthroscopy where a pericapsular nerve group (PeNG) block was complemented by injection of local anesthetic (LA) in the subpectineal plane (SPP). Methods: A mixture of 10 mL 1% lidocaine with 10 mL 1% ropivacaine and dexamethasone 4 mg was prepared. The needle was inserted under ultrasound guidance, in plane, with the probe aligned over the inguinal ligament, from lateral to medial. 10 mL of LA were injected between the psoas tendon and the pubic ramus. The needle was then re-directed and 10 mL of LA were injected in the SPP. Results: Hip arthroscopy was performed under GA, without intraoperative opioids. A multimodal analgesia regimen with iv paracetamol 1 g, tramadol 100 mg and ketorolac 30 mg was administered. The patients experienced a maximum postoperative pain score of 3/10, with no need for rescue medication. No quadriceps weakness reported. Conclusions: The anterior hip capsule is innervated by the obturator nerve (ON), accessory obturator nerve (AON) and femoral nerve (FN)3. Giron-Arango et al described the PeNG block, which targets the articular branches of FN and AON, with a potential motor-sparing effect [2]. Nielsen et al previously demonstrated [4] the ON can be reached in the SPP. In both cases, this technique was an effective 'opioid-free' analgesic method for hip arthroscopy in the ambulatory setting. Similar case reports and clinical trials are needed to validate it.